The Third Typology: The Development of Catuspatha of Denpasar City - Km. Deddy Endra Prasandya; Made Wina Satria (Architectural Research Journal, 2021)
In Bali, crossroad or pempatan agung is not only seen as a channel of movement. Crossroad or better known as catuspatha in Balinese architecture has sacred meaning and values. In the days of the kingdoms, associated with its status as the center of the royal capital, catuspatha was functioned as the natah of the city. It was the center of citizen activities. Along with the development of times, technology, and the influence of economic, social and cultural factors, the catuspatha was increasingly experiencing development and changes. This study seeks to identify the development and changes of the catuspatha of Denpasar City based on the theory of The Third Typology by Anthony Vidler. The research method used is typical normative criticism which has the belief that buildings and urban areas are always built through a model based on the types of structural, functional, and shape. The results show that The Third Typology also applies to the catuspatha of Denpasar City, where its development and changes can be seen from three typologies, including the first typology which emphasizes natural philosophy, the second typology which is more modernist ideology, and the third typology neo rationalist which emphasizes on continuity of form and history.